Intracerebral haemorrhage complicating dural arteriovenous fistula: a report of two cases. - Harding, A E (1984)
Two patients presented with unilateral peri-orbital pain, proptosis, chemosis and external ophthalmoplegia. They were shown to have dural arteriovenous fistulae related to the cavernous sinus. Intracerebral haemorrhage occurred in both patients within 18 months of presentation; this gave rise to focal seizures and signs of unilateral hemisphere dysfunction. The haematomas were in the region drained by the superficial middle cerebral vein ipsilateral to the shunt and are presumed to have been the result of locally raised venous pressure.